Analysis of Cooling Load Performance with CLTD Method Case Study: Al-Furqon Mosque - Dewanto, Ramadhan Haryo; Fahrudin; Rhakasywi, Damora (Program Studi Teknik Mesin Universitas Pamulang, 2026)
Thermal comfort in worship spaces is an important aspect that affects the quality of religious activities. However, intermittently occupied worship spaces, such as mosques during Jummah prayers, often experience spikes in heat load due to the accumulation of sensible and latent heat from occupants and solar radiation. This study aims to analyze the actual cooling load and determine the cooling load required to achieve a comfortable room temperature based on the Cooling Load Temperature Difference (CLTD) method. Temperature measurements were taken using data loggers at one outdoor point and nine indoor points during five Fridays between October 10 and November 7, 2025, from 11:00 a.m. to 1:00 p.m. Western Indonesian Time. Cooling load calculations were based on occupancy variations of 100, 300, and 600 people and comfort temperature targets of 23°C, 25°C, and 27°C. The results showed that the temperature in the worship hall was well above the thermal comfort limit. The actual cooling load increased significantly between 12:00 p.m. and 1:00 p.m. WIB and during peak occupancy, reaching a peak load of 570,116.3 Btu/h. To achieve a comfortable room temperature, the cooling capacity needs to be increased by 8–35%. The final capacity recommendation based on the measurements and ASHRAE standards ranges from 44–69 TR. It can be concluded that the cooling system of Al-Furqon Mosque is currently under capacity and requires increased capacity and adaptive operational strategies to achieve thermal comfort in intermittently occupied worship spaces in a tropical climate.